Advertısıng Elements and ıt’s Effectıveness - Tushar, Dr. Preetha Menon, Sancy Isaac George (International Journal of Advanced Science and Technology, 2020)
This study aims to study the eye movement pattern and behaviour of consumers and analyse the efficacy of print media ads in brand recall. 32 subjects were shown 7 print ads and their behavioural data was captured using Tobii eye tracking software. Three main elements of ad efficacy, Brand endorser, Product and Brand name were observed and analysed in this research. Time to First Fixation (TFF), First Fixation Duration (FFD) and Fixation Count(FC) were the indicators used to examine the eye movement pattern. The results of the study indicated that the endorser had the largest impact on the effectiveness of an advertisement. Furthermore, the respondents were interviewed and it was observed that the endorser and the product element were more effective in the successful recall of an advertisement than the brand name. ANOVA tool was used to identify which advertisement element (Endorser, Brand or Product) was most critical in attracting the consumer in print ads. The total fixation counts of endorser, brand and product were used as predictor variables to assess the ad elements. This study provides fresh data from a behavioural perspective on attention to ad elements in current times.